Big Data Vortex: Data Visualization of The Impact of The Fatwa of The Indonesian Ulema Council On Social Control of Social Media Users - Eva, Nur; Arsyiatul Alfath , Esa; Eko Wahyudi , Tedi; Myra Wahyu Arsyilia , Ern; Nugrahani, Rizka Fibria (Fakultas Psikologi Universitas Yudharta Pasuruan, 2024)
In recent times, there has been a phenomenon of social control carried out by the Indonesian Ulema Council through the MUI Fatwa Commission issued the Latest Fatwa Number 83 of 2023 concerning the Law of Support for the Palestinian Cause. The fatwa recommends Muslims avoid using Israeli-affiliated products as much as possible. These recommendations include an appeal to avoid transactions and use of products affiliated with Israel as well as those that support occupation and Zionism. Soekanto (1990) defines social control as a planned or unplanned process that aims to invite, direct, or even force certain communities or groups to comply with applicable values and norms. The purpose of this study is seeing how big the fatwa of the Indonesian Ulema Council's role is on social media users' social control.This research is a big data research with several stages, namely data collection, data has been obtained, then the pre-processing stage to data analysis in the form of visualization. The findings obtained when the fatwa was issued by the Indonesian Ulema Council on November 10, 2023, found that there was an increase in searches and trending topics on social media. On November 15, 2023, the Indonesian Ulema Council issued a statement regarding fatwa Number 83 of 2023 which did not mention specific products in terms of names, brands, and companies. After the release of the statement, there was a decrease in numbers on google trends.